Storage stability of crips measured by headspace and peroxide value analyses - R. M. Lahtinen; I. Wester; J. R. K. Niemelä (Grasas y Aceites)
Normal sunflower oil and high oleic acid sunflower oil were tested in industrial frying of crisps against the reference oil palm olein. A protective agent, dimethyl polysiloxane (DMPS), was also tested in crisp frying. Peroxide values and volatile contents of the crisps stored in normal storage conditions (room temperature) were measured during storage. From the peroxide values it could be seen that crisps fried in normal sunflower oil were the most unstable during storage. Crisps fried in high oleic sunflower oil proved to be almost as stable towards oxidation as crisps fried in reference oil palm olein. Volatile contents, measured by a static headspace - gas chromatograph - mass spectrometry system, confirmed the conclusions of peroxide analysis. Neither of the methods could find any difference between the samples which had been fried with and without DMPS.